Treatment of Non-Union with Bone Loss in Femur Fracture Using Non-vascularized Fibular Graft: A Case Report - Andriessanto Lengkong; Stefan Kambey; Rangga Rawung; Haryanto Sunarso; Albertus D. Noersasongko; Tommy Suharso; Ryan A. Senduk (e-CliniC, 2023)
Abstract: Fibula is a very versatile source of autogenous graft and has been used for decades in the field of limb reconstruction. Bony defects of the lower extremity are usually the result of high-energy trauma, tumor resection, or severe sepsis. Non-vascularized fibular graft (NVFG) is useful in the reconstruction of skeletal defects, especially in cases of scarred and avascular recipient sites, or in patients with combined bone and soft tissue defects. This study aimed to assess the effectiveness of NVFG in the management of non-union bone fracture. We reported a 16-years-old male with non-union femur fracture. Debridements were applied at the first time of admission to the hospital. Open reduction of fracture with internal femur fixation. Fibula bone was extracted as the donor of vascularized graft for the bone loss. After two years of follow-up, the patient acquired his motor functions back well, and was able to carry out daily activities as expected. In conclusion, taking together the repair and reconstruction of non-union bone in the lower extremity with NVFG and internal fixation is an effective and important option for treating non-union femoral fracture. NVFG osteosynthesis has encouraging results in such instances. It is technically less demanding, simple, and can be performed in almost all centers where image intensifier is available. Keywords: bone fracture; non-vascularized fibular graft; reconstructive microsurgery; femoral non-union